QUALITY OF LIFE AND SOME RELATED FACTORS IN ELDERLY PATIENTS WITH DEMENTIA - Tran, Viet Luc; Vu, Thu Phuong; Vu, Thi Thanh Huyen (Tạp chí Sinh lý học Việt Nam, 2023)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(–scroll-root-safe-area-inset-bottom,0px)+var(–thread-response-height))] scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-10" data-turn-id-container="request-WEB:35aba3d2-fd98-4613-9705-72e325ca48bf-10" data-testid="conversation-turn-22" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" data-conversation-screenshot-content=""> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="6a1c8358-b5ff-4494-9df9-c085f7a49fd5" data-message-model-slug="gpt-5-5" data-turn-start-message="true"> Objectives: This study aims to determine the factors associated with health-related quality of life (HRQoL) in patients with dementia at the National Geriatric Hospital. Materials and Methods: A cross-sectional study included 87 patients with dementia aged ≥60 years who were examined or treated at the National Geriatric Hospital from July 2021 to November 2021. Data were collected using designed tools that included patient characteristics. The data were entered into REDCap and analyzed using SPSS version 22.0. Results: The mean age of the participants was 76.84 ± 8.38 years. The majority of patients were female (57, 65.5%), while 30 (34.5%) were male. Overall, 42.5% (n=87) of participants had a high quality of life, whereas only 2.3% (n=87) had a poor quality of life. Slight or moderate problems were reported by 54% of participants in the mobility dimension, 42.5% in self-care, 44.8% in usual activities, 69% in pain/discomfort, and 70.1% in anxiety/depression. Severe or extreme problems were reported by 22.9% of participants in mobility, 28.7% in self-care, 49.4% in usual activities, 11.4% in pain/discomfort, and 9.1% in anxiety/depression. The mean ± SD EQ-VAS score was 57.70 ± 18.518. Depression was significantly associated with health-related quality of life (p<0.05). Conclusions: Routine health check-ups should be recommended for older adults with dementia to improve their health-related quality of life.